2022
DOI: 10.1021/acs.inorgchem.2c03287
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and Dielectric Switchable Properties of a 1D (1,1,1-Trimethylhydrazinium)PbI3 Hybrid Perovskitoid

Abstract: The synthesis and investigation of the physicochemical properties of a novel one-dimensional (1D) hybrid organic− inorganic perovskitoid templated by the 1,1,1-trimethylhydrazinium (Me 3 Hy + ) cation are reported. (Me 3 Hy)[PbI 3 ] crystallizes in the hexagonal P6 3 /m symmetry and undergoes two phase transitions (PTs) during heating (cooling) at 322 (320) and 207 (202) K. Xray diffraction data and temperature-dependent vibrational studies show that the second-order PT to the high-temperature hexagonal P6 3 /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…It turned out that both profiles show a non‐exponential pattern that indicates the presence of non‐radiative processes. [ 46 ] Both decays were fitted with a double‐exponential function and the average lifetimes were determined to be ≈400 ps and ≈50 µm for exciton and lanthanide, respectively. It was found that the values obtained for exciton for the sample synthesized as solid‐state polycrystalline powders were shorter than for their counterparts prepared as thin films [ 13 ] or colloids.…”
Section: Resultsmentioning
confidence: 99%
“…It turned out that both profiles show a non‐exponential pattern that indicates the presence of non‐radiative processes. [ 46 ] Both decays were fitted with a double‐exponential function and the average lifetimes were determined to be ≈400 ps and ≈50 µm for exciton and lanthanide, respectively. It was found that the values obtained for exciton for the sample synthesized as solid‐state polycrystalline powders were shorter than for their counterparts prepared as thin films [ 13 ] or colloids.…”
Section: Resultsmentioning
confidence: 99%
“…It takes place in some materials undergoing structural first-order phase transitions (PTs), leveraging differences in dielectric permittivity between neighboring crystal phases. Accordingly, controlling the dielectric permittivity through the selection of organic and inorganic components of HOIP compounds is vital. While the two-state switching between low and high dielectric states is a fairly common phenomenon for HOIPs in general, in the case of 1D perovskite lead iodide materials there are only a handful of instances showing this specific electric functionality. , A three-state dielectric switching is much more rare and material-demanding property, as it necessitates the presence of three structural phases within a reasonably narrow temperature range. Ideally, these phases should possess several key attributes: (i) reversibly interconvert between each other through a discontinuous PTs mechanism, (ii) feature low thermal hysteresis, and (iii) display step-like changes in the dielectric permittivity value, preferably with a high difference in ε′.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the motion of organic cations in these materials is responsible for order–disorder structural phase transitions with their symmetry breaking due to the concerted alignment of organic cations across a specific dipole moment vector direction [ 24 , 25 , 26 ]. For 1D hybrid halide perovskites, a major group of which are perovskites with face-shared octahedra assembled into the inorganic chains, organic cations are found to demonstrate behavior similar to that in their 2D counterparts [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…To study the organic subsystem of hybrid halide perovskites, neutron [ 9 ] and X-ray diffraction (XRD) [ 9 , 10 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], solid-state nuclear magnetic resonance (NMR), quasielastic neutron scattering (QENS) [ 14 , 15 , 16 , 17 ], Raman [ 10 , 11 , 12 , 13 , 21 , 22 , 23 , 24 , 33 ] scattering methods and density functional theory (DFT) modeling [ 22 , 31 , 34 ] are widely used. The vibrational properties of inorganic perovskite frameworks have been studied in the literature [ 5 , 10 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%